2023
DOI: 10.1038/s41598-023-42687-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of functional resistance training on the structure and function of the heart and liver in patients with non-alcoholic fatty liver

Ramin Jafarikhah,
Arsalan Damirchi,
Farhad Rahmani Nia
et al.

Abstract: The current study is of the quasi-experimental type, with a pre-and post-test design, and subjects were randomly assigned to one of two groups: control (n = 8) and experimental (test) (n = 8). Based on the patient's self-report and using daily diet control tables, the patient's diet planning percentage of energy supply was managed and controlled for 3 days. The protocol for functional resistance training for these circular exercises, including the squat, lunge, bear crawl, rock press, jumping jack, and back fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Montemayor et al indicated that physical activity contributes to weight loss and could be considered a therapeutic element for NAFL [50]. Jafarikhah et al suggested that resistance training could be beneficial in reducing liver fat [51]. However, Chen et al noted that physical activity alone did not improve the liver condition in individuals with liver fat accumulation [52].…”
Section: Discussionmentioning
confidence: 99%
“…Montemayor et al indicated that physical activity contributes to weight loss and could be considered a therapeutic element for NAFL [50]. Jafarikhah et al suggested that resistance training could be beneficial in reducing liver fat [51]. However, Chen et al noted that physical activity alone did not improve the liver condition in individuals with liver fat accumulation [52].…”
Section: Discussionmentioning
confidence: 99%